Effects of Different Coverage Years of Hail-Proof Nets on Environment, Leaf Traits and Fruit Quality in Apple Orchards - Junjiao Guo; Yu Guo; Panpan Tong; Xiang Wang; Jiangbo Wang (Horticulturae)
The aim of this study was to explore the impacts of hail-proof nets with different coverage years on the environment, leaf traits and fruit quality of ‘Fuji’ apple orchards, with the expectation of providing a basis for the scientific application of the coverage years of hail-proof nets. The test results indicated that hail nets with different coverage years could reduce light intensity in the orchard and increase air humidity to a certain extent, exerting a certain positive regulatory effect on the orchard’s temperature. The laying of hail nets had no significant influence on the thickness of tree foliage but significantly enlarged the leaf area. The hail nets covered for 2 years notably enhanced the chlorophyll content and photosynthetic performance of leaves. Different coverage years of hail netting had no significant effect on the fruit weight per fruit and the fruit shape index. The fruit luster gradually diminished and was significantly lower than that of the control as the coverage years increased. Further determination of the intrinsic quality of the fruits revealed that hail nets with different coverage years had no significant impact on the fruit hardness, soluble solids and total phenolic content. However, the soluble sugar, solid/acid ratio, flavonoids and vitamin C content of the fruits covered with 2-year hail nets were significantly higher than those of the other treatments. In addition, covering the hail net for 3 years significantly reduced the percentage of the sugar core fruit rate and sugar core index, while covering the hail net for 1 year, 2 years, and not covering the hail net were more effective in maintaining the sugar core index of the fruits. A comprehensive evaluation of the principal components of the hail net treatments with different coverage years demonstrated that the 2-year hail net treatment was superior to the others. In summary, covering hail nets could improve the microenvironment of the orchard, leaf traits and fruit quality to a certain degree. When the hail-proof net had been covered for more than 2 years, its protective performance and the enhancement effect on fruit quality weakened, and it was recommended that the hail-proof net should be replaced in a timely manner.